2023
DOI: 10.1155/2023/6338597
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Length of Hospital Stay and 30-Day Outcomes in Patients Admitted with Acute Decompensated Heart Failure

Abstract: Background and Aim. Regarding patients admitted with acute decompensated heart failure (ADHF), there are inconsistent reports surrounding the association between length of stay (LOS) and mortality or rehospitalization following discharge. This study evaluates the association between LOS and 30-day outcomes after discharge in patients admitted with ADHF. Method. This study is performed in the context of the Persian Registry of Cardiovascular Disease/Heart Failure (PROVE/HF). We included all patients admitted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Previous research indicates that around 60% of heart failure patients pass away within five years of their initial diagnosis [ 1 ]. It was observed that about 26% of the patients hospitalized for heart failure were hospitalized again within one month after discharge [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that around 60% of heart failure patients pass away within five years of their initial diagnosis [ 1 ]. It was observed that about 26% of the patients hospitalized for heart failure were hospitalized again within one month after discharge [ 2 ].…”
Section: Introductionmentioning
confidence: 99%